2005
DOI: 10.1029/2004gl022034
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the subducted Indian lithospheric slab in the Burmese arc

Abstract: Stress inversion of focal mechanism data in the Burmese arc region indicates distinct stress fields above and below 90 km along the subducted Indian lithospheric slab. In the upper part, the σ1 and σ3 axes trend NNE and ESE respectively, in conjunction with the ambient stress field of the Indian plate. However, in the lower part of the slab there is no preferred orientation of the σ1 or σ2 axes, but a very well defined σ3 axis is observed, that trends steeply in the down‐dip direction. It is inferred that whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…Further, the subducting Indian plate is affected by the strike slip Sagaing fault zone towards the east that would further facilitate slab break off in the upper mantle inducing deep focus earthquakes. In fact, deep focus earthquakes with hypocenters more than 90 km are concentrated towards the east (Rao and Kalpana, 2005) where the subducting Indian plate is affected by the Sagaing strike slip fault zone suggesting the importance of this fault for these earthquakes. …”
Section: Modeling Of Bouguer Anomaly Across Hindu Kush and Pamirmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, the subducting Indian plate is affected by the strike slip Sagaing fault zone towards the east that would further facilitate slab break off in the upper mantle inducing deep focus earthquakes. In fact, deep focus earthquakes with hypocenters more than 90 km are concentrated towards the east (Rao and Kalpana, 2005) where the subducting Indian plate is affected by the Sagaing strike slip fault zone suggesting the importance of this fault for these earthquakes. …”
Section: Modeling Of Bouguer Anomaly Across Hindu Kush and Pamirmentioning
confidence: 97%
“…1c shows the hypocenters of deep focus earthquakes (>90 km) of magnitude >4 since 1975 along a section 23.5°N that also shows a typical Benioff zone type distribution. Rao and Kalpana (2005) have suggested that earthquakes in this section show two broad groups, viz. earthquakes of focal depth <90 km and those with focal depth from 90 to 140 km, with the latter primarily concentrated in the eastern part.…”
Section: Introductionmentioning
confidence: 97%
“…Although the partitioning of GPS-determined deformation between permanent strain and elastic seismic cycle strain is unclear in Myanmar (but see Jade et al, 2007), geologic evidence for transpression and eastward subduction along the Arakan portion of the India-Sundaland includes well-exposed late Mesozoic ophiolite sequences (Acharyya, 2007), Neogene-Holocene deformation in the Chittagong-Tripura fold belt (Le Dain et al, 1984;Alam et al, 2003), active deformation of marine sediments in the Bay of Bengal segment of the subduction zone (Nielsen et al, 2004), and Quaternary-Holocene arc volcanoes developed on overriding Sunda lithosphere in central Myanmar (Maury et al, 2004). In addition, seismicity defi nes a well-developed east-dipping Wadati-Benioff zone down to ~150 km (Ni et al, 1989;Guzman-Speziale and Ni, 1996;Dasgupta et al, 2003;Rao and Kalpna, 2005;Stork et al, 2008;Figs. 2 and 3), and N-S-striking thrust focal mechanisms of shallow earthquakes occur in the Chittagong-Tripura fold belt and Central Burma Basin (Fig.…”
Section: Arakan Slab and India-asia-sundaland Triple Junction Regionmentioning
confidence: 99%
“…6), the fault plane with a right-lateral sense of slip is the one that best matches with the existing seismicity trend, regional fault in the vicinity and/or the known sense of fault/plate motion in the region. For instance, the right-lateral sense of plate motion is well known along the Sagaing fault (Curray et al 1979) and the Burmese arc (Rao and Kumar 1999;Rao and Kalpna 2005;Vigny et al 2003;Gahalaut and Gahalaut 2007), Kopili lineament (Vernant et al 2014) and Sikkim Himalaya (Hazarika et al 2010;Pradhan et al 2013;Fig. 2, in this paper).…”
Section: Transverse Tectonics In Sikkimmentioning
confidence: 86%
“…The cessation of the eastward subduction of the Indian plate beneath Burma and a change in the tectonic scenario to a strike-slip environment in the recent geologic times is well established (e.g. Vigny et al 2003;Rao and Kalpna 2005;Socquet et al 2006). What is interesting to understand is whether the transverse tectonics in Sikkim Himalaya due to right-lateral strike-slip movements on the Tista/Gangtok fault system, and other parts of Himalaya can be related to that observed along the Burmese arc and the Sagaing fault.…”
Section: Wrench Fault Model For Himalayamentioning
confidence: 98%